A Descriptive Study of Students’ Problems on the Use of Past Participle (V3): (A Case Study Conducted at the twelves Grade Students of SMK Negeri 1 Suwawa in Academic Year 2020/2023) - Mamonto, Asta; Miolo, Sartin T.; Napu, Novriyanto (Transbahasa, 2023)
The aims of this research is to describe what are the students’ problems on the use of past participle V3. This research took place in SMK Negeri 1 Suwawa. This research used a qualitative method and took 15 students as the participants in this research. The data collected trhough interview as the main instrument and test as the supporting instrument.The results of this research students make a lot of mistakes in determining past participle and then, the need for educators to adopt effective teaching strategies that address the challenges faced by students when it comes to using past participle. Therefore, it can be concluded that students face challenges when it comes to the use of past participle. By addressing these issues, educators can help students improve their language skills and enhance their academic and professional success. The implementation of effective teaching strategies and resources can help students to gain a better understanding of past participle and develop the skills necessary to use it correctly in various contexts.